PEMBERDAYAAN PESANTREN DALAM RANGKA KETAHANAN KOMUNITAS SOSIAL KEAGAMAAN (Studi Kasus di Pesantren Daarul Uluum Lido, Kabupaten Bogor) - , Sya'roni ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The goal of this research are photographing condition of Daarul Ullum boarding school in general, identifying Strengths, Weaknesses, Opportunities and Threats that exist, for the purposes of the empowerment of Boarding School associated with religious and social resilience. Research using qualitative methods, it is a method that focuses on data collection and analysis, while the analysis used is SWOT analysis, which has four variables , namely: Strengths, Weaknesses, Opportunities and Threats. In each variable taken a few aspects that stand out are found protruding from the real condition of Daarul Uluum Boarding School. The results of this study was Daarul Uluum Boarding School located on the first quadrant so that the empowerment of the recommended method is to expand, using the opportunity and strength to the maximum extent. Religious and social resilience is often associated with the ability to cope with risk due to social changes, economics and politics that surrounds it. A community is said to have social security if in the first place able to effectively protect its members include individuals and families who are vulnerable to social changes that affect it